Implementasi Bisnis Online Mahasiswa Jurusan Manajemen FEB Universitas Cenderawasih Dalam Menghadapi Covid-19 - Westim Ratang; Ivana Wamafma (UNIVERSITAS CENDERAWASIH, 2022)
Nowadays, in the era of technology and information, the need for media from network base can no longer be postponed. The network of internet is one of our basic needed, so we need to know and understand the virtual world. It has become a necessity to grow and develop in the world of education, in the business industry as well as for things that are social and human needed. Facing the impact of COVID-19 pandemic, it is hoped that Management Department students who have taken Entrepreneurship courses are able to capture business opportunities with online businesses. It will have an impact on more workers being laid off, because of that, we need to prepare the students of Management Department to be ready to do business online. The purpose of this activity is the implementation of application with online business in capturing business opportunities due to covid 19 pandemic for students who have take an entrepreneurship courses in the management department. The results of this service are expected that the students who have take an entrepreneurship courses, and participated in training for growing an entrepreneurial spirit, are able to have blogs to sell the products that have been produced. Through this training, students are able to join online buying and selling groups, so they are able to sell their products by E-Commers system. The use of internetbased social media to run a business has become the right choice at this time and also more efficient and effective.